Experience in the Examination of Bioequivalence Clinical Trials of Locally Applied and Locally Acting Medicinal Products in Accordance with the Eurasian Economic Union Procedures - O. Yu. Ivanova; O. L. Shikhovtsova (Регуляторные исследования и экспертиза лекарственных средств, 2024)
INTRODUCTION. The examination of protocols for clinical trials of locally applied and locally acting medicinal products highlights challenges that developers face when selecting the design, endpoints, population, comparison groups, and sample size. An analysis of the most common errors in clinical trial protocols will help minimise the number of comments from protocol reviewers and accelerate the process of bringing novel medicinal products to the pharmaceutical market.AIM. This study aimed to analyse the results of evaluating clinical trials of locally applied and locally acting medicinal products conducted with due consideration of the recent additions to the Rules for Conducting Bioequivalence Studies of Medicinal Products within the Eurasian Economic Union (EAEU); assess the main advantages of the added requirements and the challenges remaining in protocol development; and make recommendations for the most effective application of existing laws and regulations.DISCUSSION. The Rules for Conducting Bioequivalence Studies of Medicinal Products within the EAEU were supplemented with Appendices 11, 12, and 13 in August 2023. Since then, protocol reviewers have accumulated sufficient experience in the examination of clinical trial protocols for locally applied and locally acting medicinal products. This article presents the most frequent comments made during the examination of clinical trial protocols and provides recommendations for corrective actions. The most challenging aspects of drafting a protocol for a clinical trial of a locally applied and locally acting medicinal product include the selection and justification of primary/secondary endpoints and the calculation and justification of the population size. The difficulty is probably due to the lack of a detailed description of study characteristics in EAEU laws and regulations. Locally applied and locally acting corticosteroids are the least challenging medicinal products in terms of protocol drafting because EAEU legislation and scientific publications provide the most detailed guidance for them.CONCLUSIONS. The analysis of protocols for clinical trials of locally applied and locally acting medicinal products, relevant EAEU requirements, and applicable international guidelines identified several major challenges, including the selection of primary/secondary endpoints, the characterisation of the trial population, and the justification of the sample size. The recommendations presented in this article will help applicants in planning clinical trials aimed at accelerating the launch of medicinal products into the pharmaceutical market.